2019
DOI: 10.1371/journal.pone.0216616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective immune-cell depletion on growth of Mycobacterium tuberculosis (Mtb) in a whole-blood bactericidal activity (WBA) assay

Abstract: We investigated the contribution of host immune cells to bacterial killing in a whole-blood bactericidal activity (WBA) assay, an ex vivo model used to test efficacy of drugs against mycobacterium tuberculosis (Mtb). We performed WBA assays with immuno-magnetic depletion of specific cell types, in the presence or absence of rifampicin. Innate immune cells decreased Mtb growth in absence of drug, but appeared to diminish the cidal activity of rifampicin, possibly attributable to intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…More definitive transcriptome changes were seen in a previous study with drug exposure in broth cultures [3], and it is possible that the additional presence of immune cells in the WBA paradigm modifies the response to drugs. We have demonstrated that neutrophils significantly alter the bactericidal activity of rifampicin in the WBA paradigm, possibly by intracellular bacterial sequestration [28]. In an ex vivo cellular model, the response to drugs was more characteristic of host responses than of specific effects on the primary drug targets [4].…”
Section: Discussionmentioning
confidence: 91%
“…More definitive transcriptome changes were seen in a previous study with drug exposure in broth cultures [3], and it is possible that the additional presence of immune cells in the WBA paradigm modifies the response to drugs. We have demonstrated that neutrophils significantly alter the bactericidal activity of rifampicin in the WBA paradigm, possibly by intracellular bacterial sequestration [28]. In an ex vivo cellular model, the response to drugs was more characteristic of host responses than of specific effects on the primary drug targets [4].…”
Section: Discussionmentioning
confidence: 91%
“…Cross et al. reported that the rate of M.tb growth was increased in monocyte-depleted and CD66b+ neutrophil-depleted compared to un-depleted whole blood, although the inverse was true in the presence of rifampicin ( 107 ). In the O’Shea et al.…”
Section: Resultsmentioning
confidence: 99%
“…described a significant correlation between the frequencies of NK cells and production of perforin and enhanced control of mycobacterial growth in both naïve in BCG-vaccinated individuals ( 48 ). In the aforementioned study of Cross et al., the rate of M.tb growth was increased in NK-depleted compared to un-depleted whole blood in the absence of rifampicin ( 107 ). Using the cattle direct PBMC MGIA, Pepponi et al.…”
Section: Resultsmentioning
confidence: 99%